MODIFIKASI & OPTIMALISASI IPAL GEDUNG BPPT DENGAN PROSES LUMPUR AKTIF DAN BIOFILTER - Hartaja, Dinda Rita K.; setiyono, Setiyono (Center for Environmental Technology, 2015)
Prior to modification of the WWTP, BPPT building has had a domestic waste water treatment plant with a lagoon aeration system using activated sludge process. Due to the quality of the current WWTP outlet not meet quality standards waste disposal in accordance with the Governor Regulation DKI No. 122 in 2005, it is necessary to optimize the existing WWTP process and needs to be modified in order to produce quality process WWTP outlet that can meet quality standards. WWTP modification is accomplished by the addition of biofilter reactor, which has been proven reliable and stable in terms of treating domestic wastewater. Based on the monitoring results of the WWTP, it can be concluded that this system can function in accordance with the planning of the quality of the WWTP outlet which can meet the quality standards of the waste in accordance withÃ‚Â Governor Regulation DKI No. 122 2005.Keywords : Domestic wastewater, process modification, WWTP optimization.